Engineering geological study of the Kali Gandaki 'A' hydroelectric project area, western Nepal Lesser Himalaya - Kafle, K. N. (Journal of Nepal Geological Society, 1996)
The Kali Gandaki 'A' hydroelectric project area lies in the Lesser Himalayan Zone of the Syangja district of western Nepal. The rocks are characterised by highly deformed, thick sequences of the elastic rocks belonging to the Andhi Khola Formation and the carbonates of Darsing Dolomite, both belonging to the Kali Gandaki Supergroup. The dark bluish grey, brecciated and highly fractured dolomite is exposed on the abutments of the proposed diversion dam site area. It also forms steep cliffs to the north of the dam site. The contact between the dolomite and the overlying phyllite is a tectonized zone. This contact exposed along the exploratory audit and test trenches gives evidence of a fault dipping steeply towards the east. The phyllites exposed along the proposed headrace tunnel alignment and in the powerhouse site are variable in composition and rock strength. At the powerhouse area thin bands of limestone are intercalated in phyllites with sheared contacts. The headrace tunnel alignment makes acute angle with the foliation along most of the length and some sections passes parallel to the foliation. An inferred fault at about 1 km chainage, shear zones with varying thickness and a syncline at about 4 km from the intake portal are the main geological structures along the tunnel alignment which have to be carefully dealt with during the design and construction phase of the project.